Gender, caste, and asset control: Implications for agricultural projects in rice - wheat systems of Eastern India - Paris, Thelma (2014)
The CSISA project was launched in 2009 with the goal of reducing food and income insecurity in South Asia through accelerated development and deployment of new cereal varieties, sustainable crop and resource systems management practices, and better access to information. The project includes widespread delivery and adaptation of production and postharvest technologies to increase cereal production and raise income; and promotion of (i) crop and resource management practices, and (ii) high-yielding, stress tolerant and disease-and insect resistant rice, wheat and maize varieties and hybrids. GAAP looked at two different CSISA projects. This project focused on men’s and women’s different degrees of ownership, access, and decisionmaking in connection with key livelihood-sustaining assets and whether the introduction of new technologies influences these differences.